Teachers’ Adaptation In The Use of Instructional Media In Teaching English as A Foreign Language at Junior High School In Sungai Penuh - Indah Sari, Tiara; Surono, Surono; Arroyo, Estrella (Devotion : Journal of Research and Community Service, 2022)
In Indonesia, the number of English learners keep growing. Different methoods and effectiveness in teaching English has been experimented to get a better achievement. But still the systems, methods and techniques have some lacks and still need to have improvement and innovation to solve the problems. The problems are different in every schools, one of the problems currently faced by teachers was the new adaptation to the situation where schools activity turned to online activity. Teachers have to adapt into the new situation where all activities need to be handled through online activity and it becomes the problems for most of teachers who had no preparation and facilities during that time. Thus, the way English teachers adapt intstructional media and how teachers utilize and apply the instructional media especially audio visual media will be the main focus of this research. The researcher used suervey as a research design. There will be five junior high schools included in this study. There are 10 English teachers from different junior high schools in Sungai Penuh. The researcher only chose the junior high schools which are A-accredited. The researcher used questionnaire and interview as the instruments of this particular study. The researcher employed quantitative and qualitative data. The quantitative data were taken from close-ended questionnaire while the qualitative data were taken from interview result. The data analysis results shows that the teachers at Junior High Schools in Sungai Penuh used variatif instructional media in teaching. The researcher found types of audio visual instructional media mostly used among the teachers to improve student’s skills are audio recording (9,4) (hints,stories,conversation) and Videos (8,4) (documentaries,tutorials,teaching) which is very good response. The most used to improve speaking is Song (6,1) and Picture (7,3) teachers have good response towards them. Next, for reading is picture (8,8) and last to improve writing skills song (6,4), picture (6,8), flashcards (5,9), charts (5,7), videos (5,1) also have good response. Audio drama, movies, TV programs, news broadcast are the media that have bad response. Additionally, The most used hardware among the teachers are whiteboard (9,7) printed paper (9,1), smartphone (8,4), computer /laptop (7,7). Radio, recorder, CD player are get low response from the teachers. In adapting instructional media, teachers adapting from concrete object surround the classroom and schools, teachers also utilze digital devices like smartphone and software application like Whatsapp and Youtube. Moreover, teachers adapting the existing media and combined with other media that created by their own to assit them in delivering the materials. In addition, Teachers at five different junior high schools in Sungai Penuh have good views towards instructional media.